2020
DOI: 10.3390/genes11050495
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Steroidogenesis, Anti-Apoptotic Activity, and Proliferation in Porcine Granulosa Cells by RUNX1 Is Negatively Regulated by H3K27me3 Transcriptional Repression

Abstract: H3K27me3 is an epigenetic modification that results in the repression of gene transcription. The transcription factor RUNX1 (the runt-related transcription factor 1) influences granulosa cells’ growth and ovulation. This research uses ELISA, flow cytometry, EDU, ChIP-PCR, WB and qPCR to investigate steroidogenesis, cell apoptosis, and the proliferation effect of RUNX1 in porcine granulosa cells (pGCs) as regulated by H3K27me3. Decreased H3K27me3 stimulates the expression of steroidogenesis-related genes, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Our results showed that CGRP increased the protein levels of ADAM10, CR3, CX3CR1, and MCP-1 in the spinal dorsal horn and cultured microglia through EZH2, suggesting that the increased EZH2/H3K27me3 expression by CGRP might be contributed to the microglial activation and its production of inflammatory mediators, which associated with local neuroinflammation in the spinal cord. Furthermore, our results showed that CGRP could increase H3K27me3 enrichment on the genes of TRAF3IP2, BCL2L11, and ITGAM (CR3) and attenuate this mark on the genes of WNT3 and ADAM10; these might contribute to microglia proliferation, activation, and production of proinflammatory mediators by the redistribution of H3K27me3 in microglia [44]. A previous study showed that the expression of EZH2 globally increased the abundance of H3K27me3 induced both repression and activation of polycomb-regulated loci [45], similar to our results.…”
Section: Discussionmentioning
confidence: 66%
“…Our results showed that CGRP increased the protein levels of ADAM10, CR3, CX3CR1, and MCP-1 in the spinal dorsal horn and cultured microglia through EZH2, suggesting that the increased EZH2/H3K27me3 expression by CGRP might be contributed to the microglial activation and its production of inflammatory mediators, which associated with local neuroinflammation in the spinal cord. Furthermore, our results showed that CGRP could increase H3K27me3 enrichment on the genes of TRAF3IP2, BCL2L11, and ITGAM (CR3) and attenuate this mark on the genes of WNT3 and ADAM10; these might contribute to microglia proliferation, activation, and production of proinflammatory mediators by the redistribution of H3K27me3 in microglia [44]. A previous study showed that the expression of EZH2 globally increased the abundance of H3K27me3 induced both repression and activation of polycomb-regulated loci [45], similar to our results.…”
Section: Discussionmentioning
confidence: 66%
“…It was verified by ChIP-PCR that H3K27me3 occupied in enriched region of MIR143, acting as a transcriptional repressor (Figures 6A,B). Moreover, the increasing expression pattern was negative correlation with H3K27me3 decreasing expression during follicular development (Zhong et al, 2020). The methylation of H3K27 into H3K27me3 is catalyzed by histone methyltransferase EZH2, which is a member of the polycomb repressive complex 2 (PRC2), also results in PRC2 binding to the chromatin of upstream genes and the transcription start site to switch off gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-126 is a highly selective inhibitor of H3K27 methyltransferase EZH2 that reduces global H3K27me3 levels [46], whereas GSK-J4 is a potent dual inhibitor of H3K27me3/me2-demethylases JMJD3/KDM6B and UTX/KDM6A, which leads to an increase in the total nuclear H3K27me3 levels (Kruidenier et al, 2012). In this research, 6 nM GSK-126 was used to effectively inhibit H3K27me3, and 2 nM GSK-J4 was employed to effectively activate H3K27me3, as previously established (Zhong et al, 2020). The treatments for each group were triplicated, while for WB, each group contained two replicates.…”
Section: The H3k27me3 Antagonist and Agonist And Mir143 Mimics And Imentioning
confidence: 99%
“…Histone-H4 acetylation (Ac-H4) and trimethylation of histone-H3 lysine-4 (H3K4me3) are increased, whereas H3K9me3 and H3K27me3 are decreased in the promoters of LH target genes, Star and Cyp11a1 in luteinized granulosa cells after hCG injection [44]. Decreased H3K27me3 in porcine granulosa cells of Graa an follicle stimulated the expression of steroidogenesis-related genes, including Cyp11a1, Ptgs2 and Star [45]. Of critical importance, granulosa cells isolated from small follicles are not capable of undergoing luteinization when cultured with LH or forskolin+PMA, compounds that mimic LH signaling in preovulatory granulosa cells.…”
Section: Discussionmentioning
confidence: 99%